Intensive electro sintering of diamond composites with multicomponent Ni-Sn based binder - Roman Shmegera; Volodymyr Kushch (Advances in Mechanical and Materials Engineering, 2016)
This paper deals with intensive electro sintering (IES) of diamond composite materials (DCM) with multicomponent Ni-Sn based binder. The effect of the powder mixture composition, activating dopants and IES technical parameters on the formation of the microstructure and physical, and mechanical properties of DCM is studied. It has been established that the leading densification mechanisms of IES involve thermally activated plastic deformation of nickel powder particles, tin melting, and infiltration and chemical interaction of components. The presence of a liquid phase during the electro sintering increases conductivity of powder compact and intensity of heating which, in turn, significantly increases shrinkage rate and promotes uniform distribution of components and formation of intermetallic compounds. The macro-kinetic model of intermetallic compounds formation in the Ni-Sn system in non-isothermal conditions and the model of DCM with structured matrix and imperfect interface have been developed. The thermal and mechanical properties of electro sintered DCM have been evaluated. The initial mixture composition and the IES technological parameters promising in terms of DCM quality have been found. The proposed method of manufacturing the drilling bits by IES constitutes a potential basis for the industrial production technology of diamond tools.